Flying, Feathery and Beaked Objects: Children’s Mental Models About Birds - Ahi̇, Berat (International Electronic Journal of Environmental Education, 2016)
Purpose of this research is to state preschool students' mental model about birds by analyzing their drawing. This is a hermeneutical phenomenology research that is based on social constructivist philosophy. Typical case sampling method has used in order to form working group of this research. Working group consisting of 325 children who are in preschool education programs in Kastamonu Central District. Data gathered by draw and explain technique in this research. Firstly, children had asked to draw bird picture, then semi-constructed interview has made with children. By analyzing data gathered for this research, it is seen that significant amount of children drawn bird with outline drawing style ( f =167, % =51.3). 181 children ( f =181, % =55.6) drawn basic features of birds, and 83 children ( % =25.5) drawn them as behavior shown. Majority of the children said that they see birds on outdoor environments ( f =279, % =85.8), and also significant amount of children stated that the fundamental property of bird is their ability to fly ( f =127, % =39.0). After analyzing these findings, it it seen that children have non-biological based, only physical property based modal and physical mental models about birds and their natural properties. Also, it was determined that children have developed their basic knowledge of birds in outdoor environments. In light of these results, necessity of including animal and habitat education with direct-learning methods in preschool curriculum and its necessity to apply this education in outdoor mediums with direct animal observations and experiences with them are underlined.
Keywords: Birds; draw and explain; mental model; child.; 4. Education